Creating Prior Learning Assessment and Recognition (PLAR) 2001: Introduction to Reflective Practice and PLAR Portfolio Building (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
At our Canadian university, students receive credit for non-formal and informal learning by writing a competency-based portfolio. Until recently, this was largely a solitary endeavor for students, and we aimed to scale this process as many students struggled with completing a portfolio. We felt assisting students to articulate their prior learning would enable them in the process.We created the open learning course, Prior Learning Assessment and Recognition (PLAR) 2001: Introduction to Reflective Practice, and PLAR Portfolio Building. Following substantial effort, we secured institutional and governance approval for course design. Students explore reflective practice, adult learning theories, and frameworks such as Bloom's Taxonomy to identify appropriate learning levels. Our objective is to assist students in building a portfolio by mapping their learning across eight competencies.The courses address several core competencies:• Communication;• Teamwork and leadership;• Information gathering and organization;• Problem-solving and decision-making;• Numeracy;• Critical and creative thinking;• Independent learning and intellectual maturity;• Applied knowledge and skills.We followed a Community of Inquiry model, which rests on three guiding principles: focused, meaningful content; strong social connection; and invested teacher presence. To further decolonize our practice, we prioritize student choice, allowing students to present competencies in their preferred order and use provided tools to demonstrate their competencies in a variety of ways. Learners are encouraged to validate cultural knowledge and reflect on transferrable skills rooted in their unique contexts and traditions. Students were given exemplars, criteria, and examples from diverse learners so they can see where their own learning might fit into each competency.In this presentation, participants explored student activities in the new PLAR courses and accessed resources, such as the course-accompanying textbook. Participants asked questions and shared feedback on the course. By the end of the presentation, participants were able to articulate the value of competency-based assessment for their home institutions, evaluate practical PLAR activities, and reflect on their own assessor learning journeys.Attendees gained actionable tools and access to open-educational resources to enhance institutional assessment practices and support learners in validating their prior learning.Keywords: assessment, competency, pedagogy, community of inquiry